Analysis of Factors Related to Early Left Ventricular Dysfunction in Hypertensive Patients with Preserved Ejection Fraction Using Speckle Tracking Echocardiography: A Cross-Sectional Study in Vietnam - Hoang M. Tran; Hung P. Truong; Cuong C. Tran; Tuan M. Vo; Dung N. Q. Nguyen; Liem T. Dao (Diagnostics)
Objective: The purpose of this research was to assess the factors linked to early left ventricular (LV) dysfunction in hypertensive patients who have preserved ejection fraction (EF ≥ 50%) using speckle tracking echocardiography. Methods: A cross-sectional study was carried out involving 579 outpatients recruited from City International Hospital in Ho Chi Minh City using a total sampling approach, where echocardiographic measurements and clinical data were gathered and analyzed. Results: The prevalence of LV diastolic dysfunction among hypertensive individuals was found to be 45.25%, with 9.15% showing abnormal global longitudinal strain (GLS). Factors such as being over the age of 60, having diabetes, concentric LV hypertrophy, concentric LV remodeling, and LV diastolic dysfunction were identified as correlating with abnormal GLS (p < 0.05). In contrast, other cardiovascular risk factors, including smoking and dyslipidemia, did not significantly influence the GLS index (p > 0.05). Conclusions: Key factors including diabetes, diastolic dysfunction, concentric hypertrophy, and concentric remodeling of the LV are significant predictors of abnormal GLS. These results are important for the management of hypertensive patients aimed at enhancing cardiac function.